Efficacy of Intradermal Transaxamic Acid in the Treatment of Melasma: A Retrospective Study of Clinical Cases (Medical Forum Monthly, 2023)
Objective: To evaluate the efficacy of intradermal transaxamic acid in the treatment of melasma.Study Design: A Retrospective StudyPlace and Duration of Study: This study was conducted at the Dermatology Department of CMH hospital, Peshawar from June 2022 to December 2022.Materials and Methods: Pregnant and lactating mothers, those who had any medical illness, bleeding disorder, on anticoagulant therapy were not included. Injection Tranexamic acid (TA) in a concentration of 4mg/ml of distilled water in insulin syringe was used for mesotherapy. Treatment comprises of 4 session one month apart and mMASI score (Melasma Area and Severity Index) was used to assess the severity of melasma before and one month after the treatment. Side effects were noted. Patient’s level of satisfaction was recorded using 4-point scale.Results: The mean of MASI I score (before treatment) among the study participants was 12.86+5.6 and the mean MASI II after treatment with Tranexamic acid intradermally was 7.36 + 4.6. On applying the paired t test, a statistically significant difference (P= .000) among the MASI score was observed among study participants.Conclusion: Intradermal Transaxamic acid can be considered as effective and safe treatment modality for melasma to improve patients social and psychological wellbeing.